After the Conference on the Future of Europe: Time to make reforms happen:four lessons for a European Union again requiring a new balance between deepening and widening - Nicolai von Ondarza; Minna Ålander (Stiftung Wissenschaft und Politik (SWP), 2022)
The debate over major reforms of the European Union is heating up. Now that the one-year Conference on the Future of Europe has concluded, the European Parliament has proposed a convention and treaty amendments. But many national governments would still prefer to develop the European Union within the framework of the existing treaties. Closer examination of the Conference's outcomes reveals a more complex picture: citizens who expect the Union to lead the great transformation projects, who demand greater transparency, and who see treaty amendments as a means to strengthen the EU. Although the Conference failed to bring supporters and opponents of treaty amendments any closer together, the newly revived debate about deepening and widening has the potential to do so.
Keywords: 320